Przemiana koncepcji rządu tymczasowego w Bułgarii w kontekście nowelizacji konstytucji z 2023 r. i kryzysu politycznego lat 2021-2025 .......... 73 - Kumor, Kamil (Współczesne zmiany konstytucji w wybranych państwach europejskich: Pomiędzy partykularyzmem prawnym a wspólnotą doświadczeń, 2025)
TRANSFORMATION OF THE CONCEPT OF THE INTERIM GOVERNMENT IN BULGARIA IN THE CONTEXT OF THE 2023 CONSTITUTIONAL AMENDMENT AND THE POLITICAL CRISIS OF 2021-2025Since 2021, Bulgaria has been facing a serious political crisis. Attempts to form a stable majority in the National Assembly failed repeatedly, resulting in a string of early elections. During the crisis Bulgaria was governed by a series of interim governments, more dependent on the President of the Republic than on the National Assembly. As a result, political system of Bulgaria was disrupted. However, one of the few governments backed by a parliamentary majority was able to adopt a comprehensive set of constitutional amendments in December of 2023. Two of them particularly addressed the issue of interim governments. The article aims to present how the political crisis in Bulgaria unfolded and why the aforementioned amendments were passed. Moreover, it focuses on the two main aspects of those changes: the introduction of a closed list of people who may become Prime Minister of the interim government and the possibility of limitation of the powers of such government. Other noteworthy issue is the opinion of the Bulgarian Constitutional Court, which struck down many of those amendments in July of 2024. The arguments brought up in regard to the changes analyzed previously are presented. The article tries to answer the question whether the amendments to the Constitution managed to end the political crisis. In the end, the study shows the situation in Bulgarian to be an example of legal particularism.